More Than Just Numbers: Deuteronomic Influence in Hebrews 3:7-4:11 - Allen, David M. (Tyndale bulletin, 2007)
That Hebrews 3:7–4:11 alludes to the events of Numbers 14 has become an apparently established and almost universal datum of scholarship. This paper, however, argues that Hebrews’ rhetoric in the pericope and its exegesis of Psalm 95 is better explained by appealing to a Deuteronomic perspective, rather than that of Numbers. The bipartite structure of the psalm itself evinces a quasi-Deuteronomic choice that echoes the decision which Hebrews lays before its audience, and it utilises language that is quintessentially Deuteronomic. Four key words in 3:7-19 are subsequently discussed and it is demonstrated that their context and provenance is not Numbers 14, but rather the particular milieu of Deuteronomy. Whilst the contribution of Numbers 14 to the pericope is not to be dismissed, Hebrews’ use of the psalm appears to be more orientated towards a Deuteronomic perspective.